2018
DOI: 10.1080/21663831.2018.1462266
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic reduction of void swelling by helium in ion-irradiated high purity α-iron

Abstract: Effect of helium on void swelling was studied in high-purity α-iron, irradiated using energetic selfions to 157 displacements per atom (dpa) at 773 K, with and without helium co-implantation up to 17 atomic parts-per-million (appm) He/dpa. Helium is known to enhance cavity formation in metals in irradiation environments, leading to early void swelling onset. In this study, microstructure characterization by transmission electron microscopy revealed compelling evidence of dramatic swelling reduction by helium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…There is an open question as to whether H enhances [361] or reduces [324] swelling in steels. Similarly, helium can both increase and decrease swelling depending on the density of preexisting or irradiation-induced cavities [362] .…”
Section: Discussionmentioning
confidence: 99%
“…There is an open question as to whether H enhances [361] or reduces [324] swelling in steels. Similarly, helium can both increase and decrease swelling depending on the density of preexisting or irradiation-induced cavities [362] .…”
Section: Discussionmentioning
confidence: 99%
“…The observed opposite trend of He effect on dispersoids appears to be quite similar to the often-observed He effect on swelling. In previous helium co-implantation studies on various non-ODS alloys, it has been reported that helium does not always increase swelling [40,41,42,43]. Void swelling increased for low He/dpa levels and decreased for high He/dpa levels.…”
Section: Discussionmentioning
confidence: 91%
“…Since cavities are thought to be neutral sinks for both interstitials and vacancies, defect recombination is promoted instead of biased vacancy trapping. This leads to limited and saturated void growth [43].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the free surface on microstructure evolution is significant which acts as a neutral point defect (PD) sink [30,31]. Due to the enhanced recombination at or adjacent to a free surface, areas devoid of any irradiation induced damage (denuded zones) are often observed [32,33]. Most importantly, maximum damage occurs close to the ion projected range where the injected ions deposited into the material can artificially suppress cavities at and around the damage peak [30,31,[33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the enhanced recombination at or adjacent to a free surface, areas devoid of any irradiation induced damage (denuded zones) are often observed [32,33]. Most importantly, maximum damage occurs close to the ion projected range where the injected ions deposited into the material can artificially suppress cavities at and around the damage peak [30,31,[33][34][35][36][37][38][39][40]. For example, recent ion irradiation experiments at 500 °C up to 157 dpa using self-ions on high purity bcc Fe observed nearly one-third reduction of void swelling at the damage peak as compared to mid-range [33].…”
Section: Introductionmentioning
confidence: 99%